Penerapan Metode Preference Selection Index (Psi) Dalam Perekrutan Pengajar Komputer Di Ibay Komputer Rantauprapat - Purnama Sari, Ira (Buletin Ilmiah Informatika Teknologi, 2025)
Ibay Computer is a Course and Training Institute that focuses on Computer Technology. This institution requires teachers who are qualified and professional in their fields, however, the process of recruiting teachers at the institution has so far not been effective and does not have good standards, which has caused the institution to experience ups and downs in the number of students. Based on these problems, to help institutions, a Decision Support System is needed with support using the Preference Selection Index (PSI) Method. This system is designed to assist decision making in solving problems by sorting the highest ranking values ​​to provide decision recommendations. The decision support system for recruiting new Ibay Computer Rantauprapat teachers using the PSI method can be implemented well and has very good performance when seen from the results of accuracy testing. By applying the PSI method, Nurmayana Sari will receive the highest ranking as a computer teacher with a total score of 1,000.